MODERN APPROACHES TO THE DEVELOPMENT OF ADAPTIVE SPORTS AND PHYSICAL EDUCATION IN UKRAINE: THE CONCEPT OF A HYBRID MODEL (Physical Culture and Sport: Scientific Perspective, 2025)
The article substantiates the concept of a hybrid Ukrainian model of the development of adaptive physical education and sports activities, which combines international standards with Ukrainian realities. The war in Ukraine led to an unprecedented increase in the number of veterans and people with disabilities, which made it necessary to create a systemic model for the development of adaptive sports and physical education.The purpose of the article is to scientifically substantiate a hybrid Ukrainian model of the development of adaptive physical education and sports activities, which integrates international standards (ICF, IPC Classification Code, coaching training framework) taking into account specific Ukrainian ones.The international experience of Canada, Poland, Lithuania, Japan and South Korea, which have their own national models for the development of adaptive sports and physical education, is analyzed. In Canada, adaptive sports are integrated into the national Active Living strategy, in Poland and Lithuania, state support is combined with the activity of local communities, in Japan, a strategic plan for the development of sports and physical education with an emphasis on innovative technologies has been implemented, in South Korea, adaptive sports are integrated into the health care system. The Ukrainian model should be based on international standards (WHO, 2001; IPC, 2024; ICCE, 2013), but take into account national conditions: a high number of veterans, limited funding and regional imbalances. The proposed architecture includes management and financial, educational and personnel, infrastructure and social integration blocks. The logical and structural scheme provides for the transformation of resources into processes and results leading to the final consequences - improving health, social integration and compatibility with the international system. The implementation of the model will ensure the sustainability of programs and integrate the Ukrainian system of adaptive physical education and sports activities into the international space.
Keywords: adaptive sports; adaptive physical education; adaptive physical education and sports activities; hybrid model concept; persons with disabilities; social integration